Checkbook Diplomacy Jepang dalam Hubungan dengan ASEAN: Relevansi dan Tantangan bagi Indonesia - Hadi, Syamsul (UI Scholars Hub, 2009)
This article would analyze the increasing of Japanese interest in its relations with ASEAN in the contemporary era, with the emerging of China, the withdrawal of substantive parts of the US presence in East Asia, and the intensification of economic integration in ASEAN. It is argued that Japan would continually use its method of ‘checkbook diplomacy’ in dealing with ASEAN, due to its inability to reformulate a new international role to adjust the international situations. As the de facto leader of ASEAN in line with Indonesian national interests as well as ASEAN regional visions.